2013
DOI: 10.1002/rds.20056
|View full text |Cite
|
Sign up to set email alerts
|

Passive all‐sky imaging radar in the HF regime with WWV and the first station of the Long Wavelength Array

Abstract: [1] We present a new passive, bistatic high-frequency (HF) radar system consisting of the transmitters for the radio station WWV and the dipole antenna array that comprises the first station of the Long Wavelength Array (LWA) or "LWA1." We demonstrate that these two existing facilities, which are operated for separate purposes, can be used together as a unique HF radar imager, capable of monitoring the entire visible sky. In this paper, we describe in detail the techniques used to develop all-sky radar capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In particular, the all-sky imaging capability and bistatic nature of the LWA1+WWV system manifest a probe of E s structures that can pinpoint their horizontal positions to a precision as good as 1 km over a relatively large area (∼100 km wide and several hundred kilometers long). This is discussed at greater length by Helmboldt et al (2013).…”
Section: Lwa1 Wwv Fais and Meteor Trailsmentioning
confidence: 94%
See 4 more Smart Citations
“…In particular, the all-sky imaging capability and bistatic nature of the LWA1+WWV system manifest a probe of E s structures that can pinpoint their horizontal positions to a precision as good as 1 km over a relatively large area (∼100 km wide and several hundred kilometers long). This is discussed at greater length by Helmboldt et al (2013).…”
Section: Lwa1 Wwv Fais and Meteor Trailsmentioning
confidence: 94%
“…In this case, the "targets" are E s layers and meteor trails. Specifically, Helmboldt et al (2013) showed that the HF transmitters of the NIST radio station WWV near Ft. Collins, Colorado (see Fig. 1), could be used with LWA1's TB modes to probe the ionosphere.…”
Section: Lwa1 Wwv Fais and Meteor Trailsmentioning
confidence: 99%
See 3 more Smart Citations